Methane-Rich Saline: A Potential Resuscitation Fluid for Hemorrhagic Shock. (26th November 2019) - Tong, Yingmu; Dong, Yanyan; Feng, Yang; Li, Zeyu; Jia, Yifan; Zhang, Xing; Qu, Kai; Liu, Chang; Zhang, Jingyao
Abstract : Hemorrhagic shock is caused by massive blood loss. If the patient is not fully resuscitated in time, this may eventually lead to multiple organ failure and even death. Previous studies on methane-rich saline in animal models showed that it confers resistance against many diseases. In this study, we explored the protective effect of methane-rich saline, used as a resuscitation fluid, in hemorrhagic shock. Hemorrhagic shock was induced in SD rats by bloodletting via intubation of the right femoral artery. The rats were divided into three groups: a sham control group (sham control), a shock group resuscitated by an infusion of autologous blood and an equivalent volume of normal saline (Shock+NS), and a shock group resuscitated by an infusion of autologous blood and an equivalent volume of methane-rich saline (Shock+MRS). Assessment of blood pressure and levels of plasma lactate showed that resuscitation using methane-rich saline (MRS) restored systemic blood pressure and reduced the levels of lactate in the plasma. Meanwhile, lower levels of serum IL-6 and TNF- α were also observed in the group resuscitated with MRS. In the heart, liver, and kidney, MRS reduced inflammation and oxidative stress levels. Analysis of organ function via levels of biochemical indicators revealed that the group resuscitated with MRS had reduced serum levels of AST and CK, indicating a potential cardioprotective effect. The expression levels of apoptosis-related proteins, including those of Bcl-2/Bax, and the results of TUNEL-labeling assay indicated that MRS significantly reduced apoptosis in the heart. Methane also had a positive effect on the expression of the PGC-1 α /SIRT3/SOD2 signaling pathway. Our results showed that MRS can potentially serve as a novel resuscitation fluid because of its anti-inflammatory, antioxidative, and antiapoptotic properties.